PELAKSANAAN PENYALURAN WAKAF UANG DALAM UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT PADA BADAN WAKAF INDONESIA PERWAKILAN PROVINSI RIAU - Derisma Wulandari; Mardalena Hanifah; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Cash waqf is a legal act of waqf by separating or donating a portion ofone's money to be used for a specified period of time or forever in accordancewith the interests of the waqif used for the purposes of worship or welfare of thepeople according to Sharia law. In its implementation, there was a delay in thedistribution of cash waqf funds raised to be used to improve the welfare of thepeople. Currently, the Indonesian Waqf Agency (BWI) representative for Riauprovince is facing difficulties in managing and introducing cash waqf to thepublic. The community does not see the real results of cash waqf and does notunderstand the concept and existence of cash waqf, even though cash waqf has thepotential to improve people's well-being. The aim of writing this thesis is firstly tofind out the implementation of cash waqf distribution in an effort to strengthen thepeople's economy at the BWI representative of Riau province, secondly to find outthe obstacles and efforts in the implementation of cash waqf distribution in aneffort to strengthen the people's economy at BWI Representative of Riau Province.This research is classified as empirical legal research, namely researchinto the effectiveness of law, how law functions in society. This study wasconducted at the BWI Representative Office of Riau Province, while thepopulation and sample were waqf and waqf management and developmentdivisions related to the issues studied in this study, the data sources used wereprimary data and secondary data, data collection techniques in this studyconsisted of interviews and literature review, after the data were collected andthen analyzed to draw conclusions.The results of the investigation can be concluded: First, the BWIrepresentative of Riau Province is still in the fundraising stage and has beendeposited with the Sharia Financial Institution Receiving Money Waqf. Second,Cash waqf cannot be distributed because there is no Sharia Guarantee Institutionas guarantor or supervisor over the principal amount of the waqf to be managed.Efforts made are the existence of a governor's circular. The author's suggestionis, first, that BWI immediately distributes the benefits of cash waqf. Second, thereare regulations regarding the procedures for managing and developing cash waqffrom the Sharia Guarantee Institution's side.Keywords: Implementation - Cash Waqf - Public Welfare